Cascade of Misalignment: Understanding Coaching Erosion in Hierarchical Organizations - Iwan Pramana (Goodwood Publishing, 2026)
Purpose: This study explores why coaching initiatives fail to deliver sustained developmental impact in hierarchical and compliance-driven organizations using the Indonesian banking sector as a context. Research Methodology: This qualitative study was conducted in Indonesia using Gioia’s methodology to examine why coaching initiatives do not deliver sustained developmental impact in hierarchical banking organizations. Data were collected through semi-structured interviews with 23 professional coaches and triangulated with classroom observations and peer debriefing. The data were manually coded using Microsoft Excel (no software-based CAQDAS was used). Thematic analysis was applied to identify first-order concepts, second-order themes, and aggregate dimensions using interpretive logic. Results: Coaching becomes ineffective as a cascade of misalignment starts with role confusion and behavioral gaps, escalating into symbolic and reactive implementation, and culminating in cultural and structural barriers, such as fear of openness and strategic drift. These dynamics create a recursive breakdown that weakens coaching effectiveness despite formal institutional support. Conclusions: Coaching ineffectiveness in hierarchical organizations emerges not from isolated deficiencies, but from a cumulative cascade of misalignment across individual understanding, managerial practice, and structural–cultural conditions. Limitations: This study focuses on a specific sector (banking) and draws data primarily from coach perspectives. Broader generalizability may require further multi-actor and cross-industry studies. Contributions: This study contributes to human resource development (HRD) theory by offering a multilevel explanation of coaching erosion and proposing a conceptual framework to help organizations realign coaching strategies with structural and cultural realities.